Numerical Green's Function-Based Method for Modeling Radiated Emission From PCBs in Shielding Enclosures - Wang, Zi An; Jiang, Li Jun; Mao, Jun Fa; Li, Ping (IEEE transactions on microwave theory and techniques)
Due to stringent electromagnetic compatibility (EMC) regulations, all electronic devices need to go through rigorous radiated emission tests before launching to market. Thus, efficient, accurate, and cheap characterization approaches are quite of interest. Instead of utilizing the time-consuming and expensive direct far-field measurement, in this work, a novel methodology on the basis of numerical Green's function (NGF) is proposed to acquire the parasitic EM emissions from PCBs placed in a shielding enclosure with ventilation slots. Referring to Schelkunoff's equivalence principle, the whole modeling procedure can be decomposed into two steps in order to obtain the emissions in the entire space. For the first step, the tangential electric fields over the surface of ventilation slots are sampled first; then, the NGF over a spherical surface tightly enclosing the perfectly electric conductor (PEC) filled shielding box is numerically evaluated; finally, the tangential component of the magnetic field over the spherical surface enclosing the shielding box is calculated in terms of the NGF and the sampled near electric field. As for the second step, by filling the sphere with a perfectly magnetic conductor (PMC) first, the pertinent Green's function is further expanded by the spherical modal functions; later, the radiated emission outside this sphere can be analytically evaluated in terms of the previously obtained tangential magnetic field and the modal function expanded Green's function. Therefore, the novelty of the proposed method has two folds: 1) only the tangential electric field over the ventilation slots is required, thus saving a lot of time in near-field measurement and 2) the NGF is independent of the PCBs in the shielding enclosure and, thus, only needs to be calculated once even though the PCBs inside the shielding enclosure is changed. To validate and verify the effectiveness of this proposed modality, several representative examples are presented.